Effect of intravitreal anti-vascular endothelial growth factor on corneal endothelial cell count and central corneal thickness in Indian population - Mukesh Joshi; Mayuresh P Naik; L Sarkar (Journal of Family Medicine and Primary Care, 2019)
Purpose: To evaluate the effect of intravitreal anti-VEGF on corneal endothelial cell count and central corneal thickness as well as to compare these in phakic and pseudophakic eyes. Material and Methods: The study was conducted in 102 eyes selected, as per selection criteria, over a time period of 18 months. At first patient visit, examination included: 1. Fundus examination. 2. Specular microscopy was done to look for endothelial cell count and Central corneal thickness. At second visit, Injection 0.5 mg/0.05 ml of ranibizumab was administered. Visits at day 1, day 7 and 1 month were done for Endothelial cell density and central corneal thickness was measured by specular microscope Results: The mean CCT value in pseudophakic group was 502.08 ± 19.91, 501.9 ± 20.31, and 501.72 ± 21.55 on day 1, 7 and 30, respectively. The mean CCT value in phakic group was 506.53 ± 22.61, 505.96 ± 20.12, 505.92 ± 20.3 and 505.69 ± 21.47. The mean value of ECD in pseudophakic eyes on day 1, 7, and 30 were 2284.24 ± 299.86, 2281.39 ± 289.46 and 2284.06 ± 312.65 cells/mm2, respectively. The mean value of ECD in phakic eyes on day 1, 7, and 30 were 2314.51 ± 212.08, 2313.92 ± 212.7 and 2313.63 ± 216.86 cells/mm2, respectively. Conclusion: There is no significant change in endothelial cell density, central corneal thickness, coefficient of variation and intraocular pressure before and after intravitreal injection over one month of follow-up. The results are similar between phakic and pseudophakic eyes.